Stress “deafness” in a Language with Fixed Word Stress: An ERP Study on Polish - Domahs, Ulrike; Knaus, Johannes; Orzechowska, Paula; Wiese, Richard (Frontiers in Psychology, 2012)
The aim of the present contribution was to examine the factors influencing the prosodic processing in a language with predictable word stress. For Polish, a language with fixed penultimate stress but several well-defined exceptions, difficulties in the processing and representation of prosodic information have been reported (e.g., Peperkamp & Dupoux, 2002). The present study utilized event-related potentials (ERPs) to investigate the factors influencing prosodic processing in Polish. These factors are i) the predictability of stress and ii) the prosodic structure in terms of metrical feet. Polish native speakers were presented with correctly and incorrectly stressed Polish words and instructed to judge the correctness of the perceived stress patterns. For each stress violation an early negativity was found which was interpreted as reflection of an error-detection mechanism, and in addition exceptional stress patterns (= antepenultimate stress) and post-lexical (= initial) stress evoked a task-related positivity effect (P300) whose amplitude and latency is correlated with the degree of anomaly and deviation from an expectation. Violations involving the default (= penultimate stress) in contrast did not produce such an effect. This asymmetrical result is interpreted to reflect that Polish native speakers are less sensitive to the default pattern than to the exceptional or post-lexical patterns. Behavioral results are orthogonal to the electrophysiological results showing that Polish speakers had difficulties to reject any kind of stress violation. Thus, on a meta-linguistic level Polish speakers appeared to be stress-‘deaf’ for any kind of stress manipulation, whereas the neural reactions differentiate between the default and lexicalized patterns.